Harrisons principles of internal medicine, twentieth edition (vol.1 & vol.2 - Loscalzo, Joseph (harvard Medical School Boston); Jameson, J. Larry (New York : McGraw-Hill Education, 2018)
"Harrison's is intended for learners throughout their careers. For students, Part 1, Chapter 1 begins with an overview of "The Practice of Medicine". In this introductory chapter, the editors continue the tradition of orienting clinicians to the science and the art of medicine, emphasizing the values of our profession while incorporating new advances in technology, science, and clinical care. Part 2, "Cardinal Manifestations and Presentation of Diseases" is a signature feature of Harrison's. These chapters eloquently describe how patients present with common clinical conditions, such as headache, fever, cough, palpitations, or anemia, and provide an overview of typical symptoms, physical findings, and differential diagnosis. Mastery of these topics prepares students for subsequent chapters on specific diseases they will encounter in courses on pathophysiology and in clinical clerkships"--
Includes bibliographical references and index.
Keywords: internal medicine